Credit Risk and Financial Performance of Selected Commercial Banks in Kampala District, Uganda. A Cross-sectional Study - Bakashaba , Edmand; Lutaaya, Josephine Miremba; Arinaitwe , Hope (Student's Journal of Health Research Africa, 2022)
Background: The main purpose of the study is to examine the relationship between credit risk and the financial performance of commercial banks in Uganda by; examining the relationship between default risk and financial performance and examining the relationship between recovery risk and financial performance of commercial banks. Methodology: The study used a descriptive, correlational and cross-sectional research design. It also adopted both quantitative and qualitative survey designs. The study sample size comprised of 130 employees of the selected commercial banks in the Kampala Central business district. Further, the study used a questionnaire as a research instrument and simple random sampling to collect data. Results: The findings revealed that the average loan approval period was 2.65 weeks with a minimum of 1 and maximum of 5 weeks. This signifies inefficiency as customers may not use the borrowed funds for its intended purpose as money comes after a long time. Further, the results show that customers must at least wait for two weeks to access a loan. The findings of the Kaplan plot showed a negative relationship between loan period and recovery rate. Further, there is a steep fall in the recovery of loans after 6 months. The findings revealed r = 0.441 correlation coefficient and a sig value of 0.00. This indicated a significant positive relationship between recovery risk and financial performance of commercial banks. The correlation between default risk and financial performance of the selected commercial banks was -0.476. Therefore, there is a negative significant relationship between default risk and financial performance of commercial banks. Conclusion: Generally, there was a relationship between credit risk and financial performance of the selected commercial banks. Recommendation: The selected commercial banks need to improve efficiency in operations by reducing on the loan approval period to at least one week.